Freshwater conditions in early Paleolake Olduvai from the Naibor Soit Formation - Daniel Gebregiorgis; Nabil Murshed; Lindsay J. McHenry; Francis Muchemi; Lisa Duong; Jennifer G. Bash; Jackson K. Njau; Ian G. Stanistreet; Harald Stollhofen; Kathy D. Schick; Nicholas Toth; Gail M. Ashley; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The COSPAR international space weather action teams (ISWAT) initiative: a driving force for the COSPAR space weather roadmap - Maria M. Kuznetsova; Mario M. Bisi; Hermann J. Opgenoorth; Martin A. Reiss; M. Leila Mays; Lucilla Alfonsi; C. Nick Arge; David Barnes; Anna Belehaki; Thomas E. Berger; Amanda Brecht; Sean Bruinsma; et al. (Advances in Space Research, 2026)

The USGS Rotating X-Ray Computed Tomography (RXCT) Coral-Core Archive: Scope, Access, and Standardization - Ferdinand K. J. Oberle; Lauren T. Toth; Nancy G. Prouty; Brooke Santos; Jessica A. Jacobs; Sierra Bloomer; Kian Bagheri; Breanna N. Williams; Jason S. Padgett; Anastasios Stathakopoulos; SeanPaul La Selle (Journal of Marine Science and Engineering, 2026)
We announce the U.S. Geological Survey (USGS) Rotating X-ray Computed Tomography (RXCT) Coral-Core Archive, a digital resource derived from ~360 coral reef cores curated at the USGS Pacific and St. Petersburg Coastal and Marine Science Centers. The archive delivers calibrated 3-dimensional image volumes that enable reproducible values of skeletal density, linear extension, and calcification from decadal- to centennial-scale records of coral growth and bioerosion. Cross-study comparability within the archive is supported by a unified RXCT workflow that minimizes imaging artifacts. This includes rejecting image-intensity–density calibrations with r2

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Luminescence and radiocarbon dating the Naisiusiu Beds type section and timing of the Middle Stone Age/Later Stone Age transition at Olduvai Gorge, Tanzania - Ian G. Stanistreet; Harald Stollhofen; Rachel K. Smedley; Kaja Fenn; Stanley H. Ambrose; Jackson K. Njau; Kathy Schick; Nicholas Toth (Journal of Human Evolution, 2025)

Land-based nutrient flux to a fringing reef: insights from Ofu Island, American Samoa - Nancy G. Prouty; Ferdinand K. J. Oberle; Olivia M. Cheriton; Lauren T. Toth; Eric K. Brown; Curt D. Storlazzi (Frontiers in Marine Science, 2025)
Submarine groundwater discharge (SGD) can be a critical driver of nutrient transport to coral reef ecosystems, shaping water quality, primary productivity, and overall reef health. This study quantifies SGD fluxes and associated nutrient dynamics in two reef flat pools within the National Park of American Samoa on Ofu Island: Papaloloa Point and Fattuana Point. A multi-method approach integrating multichannel electrical resistivity tomography (ERT), unoccupied aerial system-based thermal infrared (UAS-TIR) surveys, radon-based SGD measurements, and discrete water sampling was used to assess SGD rates and nutrient contributions to nearshore pools. UAS-TIR imagery revealed cooler sea-surface temperatures relative to ambient seawater emanating from coastal point sources in both pools, indicative of SGD, with higher fluxes observed at Papaloloa Point. Time-series radon measurements revealed a strong inverse correlation between calculated SGD rates and tidal stage, further indicative of SGD. The SGD response was immediate (i.e., in phase with the tides) at Papaloloa Point, likely due to its highly permeable calcareous sand and gravel substrate. In contrast, a 2–3-hr lag in SGD response at Fattuana Point indicates discharge from a more inland aquifer with lower transmissivity. Nutrient concentrations correlated directly with temperature and salinity, confirming SGD as the dominant nutrient transport mechanism, whereas isotopic analyses demonstrated inputs from both groundwater and potential anthropogenic sources. These findings underscore the complexity of SGD-mediated nutrient dynamics in coral-reef environments and emphasize the need for an integrated geochemical and geophysical approach to support effective coral-reef conservation and management strategies.

Age-related and dual task-induced gait alterations and asymmetry: optimizing the Semmelweis Study gait assessment protocol - Peter Mukli; Mihaly Muranyi; Ágnes Lipecz; Zsofia Szarvas; Tamás Csípő; Anna Ungvari; Mónika Fekete; Vince Fazekas-Pongor; Anna Peterfi; Ágnes Fehér; Norbert Dosa; Noémi Mózes; et al. (GeroScience, 2025)
Gait alterations are recognized as early markers of age-related decline and cognitive impairment. Dual-task assessments, which impose cognitive load while walking, provide valuable insights into gait control limitations and cognitive-motor interactions in aging populations. This study evaluates age-related and cognitive load-induced changes in gait parameters, with a particular focus on asymmetry, and aims to optimize the gait assessment protocol for the Semmelweis Study framework. The Semmelweis Study is a large-scale workplace cohort investigating the determinants of unhealthy aging and promoting healthy brain aging by identifying risk factors and protective mechanisms influencing vascular, metabolic, and neurocognitive decline. As part of this initiative, gait analysis is emerging as a critical tool for assessing functional aging, detecting early signs of mobility and cognitive impairment, and contributing to biological age assessment. A cross-sectional analysis was conducted on adults aged 23 to 87 years using a pressure-sensitive walkway system. Participants were evaluated under single-task conditions (normal walking) and dual-task conditions (walking while performing a concurrent cognitive task). Spatiotemporal gait parameters, asymmetry indices, and dual-task costs were analyzed to assess age-related changes in gait performance and cognitive-motor interactions. Aging was associated with significant reductions in gait speed, step length, and stride length, along with a corresponding increase in gait asymmetry. Dual-task conditions exacerbated these alterations, indicating age-related impairments in cognitive-motor integration. Asymmetry indices were sensitive to aging effects, suggesting their potential as biomarkers for functional decline. The dual-task cost on gait was significantly greater in older adults, reinforcing the interplay between cognitive and motor systems in aging. Age-related gait alterations, particularly under cognitive load, underscore the importance of comprehensive gait assessments in aging research. Our findings contribute to the optimization of the Semmelweis Study gait assessment protocol by identifying key gait parameters that capture functional decline and biological aging. Integrating dual-task gait analysis into large-scale epidemiological studies has the potential to enhance early detection of brain health decline, refine biological age estimation, and guide targeted interventions to support healthy aging and neuromotor resilience.

Evaluating the effectiveness of field-based probiotic treatments for stony coral tissue loss disease in southeast Florida, USA - Kelly A. Pitts; Mackenzie Scheuermann; Jonathan S. Lefcheck; Blake Ushijima; Natalie Danek; E. Murphy McDonald; Aaron R. Milanese; Monica D. Schul; Julie L. Meyer; Kathryn A. Toth; Zachary Ferris; Yesmarie T. De La Flor; et al. (Frontiers in Marine Science, 2025)
Stony coral tissue loss disease (SCTLD) has spread throughout Florida’s Coral Reef, causing extensive mortality of over 30 species of reef-building corals, and has rapidly spread to many other countries and territories throughout the Caribbean. Current treatments for SCTLD, including a proprietary paste mixed with the antibiotic amoxicillin, do not provide protection from future infections and may select for antibiotic-resistant pathogenic bacteria. In contrast, beneficial microorganisms (i.e., probiotics), may directly treat or act as prophylactics for corals exposed to SCTLD. This study investigated the use of the bacterium Pseudoalteromonas sp. McH1-7, previously isolated from a SCTLD-resistant fragment of Montastraea cavernosa , as a potential probiotic treatment for SCTLD-infected M. cavernosa colonies in the wild. We developed and tested two probiotic deployment methods: (1) the injection of a probiotic in seawater suspension into a weighted bag placed over the coral to treat the whole colony; and (2) a sodium alginate-based paste that was applied directly to each disease lesion. After treatment, the disease progression of each colony was routinely monitored using three-dimensional photogrammetry for 2.5 years. Slurries of tissue and mucus samples were taken from healthy and diseased colonies before treatment, two weeks after treatment, and three months after treatment to identify possible shifts in bacterial and archaeal communities. McH1–7 successfully slowed SCTLD lesion progression for 2.5 years following treatments when delivered using the whole-colony treatment technique. Our assessment of the microbiome following treatment showed that McH1–7 was effective without dominating bacterial communities among infected corals. In contrast, corals treated with the probiotic paste lost more tissue than corals treated with the control paste, indicating that the lesion-specific probiotic paste is not effective at stopping SCTLD. Probiotic inoculations via a whole-colony treatment technique may provide a path toward slowing the loss of reef-building corals due to SCTLD.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Insecticide application prevents honey bees from realizing benefits of native forage in an agricultural landscape - Ashley L. St. Clair; Adam G. Dolezal; Randall P. Cass; Harmen P. Hendriksma; David S. Stein; Kate E. Borchardt; Erin W. Hodgson; Matthew E. O'Neal; Amy L. Toth (Science of The Total Environment, 2025)

GeoGOBLIN: A catchment-scale land balance model for assessment of climate mitigation pathways considering environmental trade-offs for multiple impact categories - Colm Duffy; Daniel Henn; David Styles; Gregory G. Toth; Remi Prudhomme; Pietro P.M. Iannetta; Ken Byrne (Environmental Modelling & Software, 2024)

Age-depth model for uppermost Ndutu Beds constrains Middle Stone Age technology and climate-induced paleoenvironmental changes at Olduvai Gorge (Tanzania) - Rachel K. Smedley; Kaja Fenn; Ian G. Stanistreet; Harald Stollhofen; Jackson K. Njau; Kathy Schick; Nicholas Toth (Journal of Human Evolution, 2024)

Science opportunities with solar sailing smallsats - Slava G. Turyshev; Darren Garber; Louis D. Friedman; Andreas M. Hein; Nathan Barnes; Konstantin Batygin; Michael E. Brown; Leroy Cronin; Artur R. Davoyan; Amber Dubill; T. Marshall Eubanks; Sarah Gibson; et al. (Planetary and Space Science, 2023)

Agroforestry contributions to smallholder farmer food security in Indonesia - Colm Duffy; Gregory G. Toth; Robert P. O. Hagan; Peter C. McKeown; Syed Ajijur Rahman; Yekti Widyaningsih; Terry C. H. Sunderland; Charles Spillane (Agroforestry Systems, 2021)
Agroforestry has potential for strengthening the climate change resilience of smallholder farmers in Southeast Asia. In Indonesia, the food security challenges faced by smallholders will likely worsen due to climate change impacts. Agroforestry provides and option for strengthening climate change resilience, while contributing to food access, income, health, and environmental stability. To evaluate the evidence for such benefits, this systematic review identifies 22 peer-reviewed articles published between 2000 and 2019 which assess agroforestry’s contributions to food security in Indonesia, mostly in Java or Sumatra. Analysis of the studies indicate that traditional and commercial agroforestry contribute to food security in diverse ways: for example, traditional homegardens offer 20% more dietary diversity than commercial counterparts, while commercial homegardens may contribute up to five times more income. Agri-silviculture contributions fall along a timber versus non-timber forest product continuum that displays a similar tradeoff between diversity and income. Those systems with a commercial focus may receive 54% of their income from a single commodity crop such as coffee, while traditional systems allow greater access to plants with medicinal benefits. Nearly all agroforestry systems offered indirect benefits for food security, such as allowing more off-farm work than traditional agriculture and contributing to environmental stability: users of agroforestry were found by one study to collect 83% less fuelwood from natural forests. One study highlighted that agroforestry options have up to 98% greater net present value (for periods over 30 years) compared to slash and burn style agriculture. However, very few studies of Indonesian agroforestry focused explicitly on financial analysis and food security, indicating the need for further research. Given the similar situations faced by many Southeast Asia countries, our findings contribute to emerging trends throughout the region regarding the relationship between agroforestry and food security.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

Correction to: Primary immunodeficiencies in Central and Eastern Europe—the power of networking Report on the activity of the Jeffrey Modell Foundation Centers Network in Central and Eastern Europe - A. Sediva; M. Bataneant; M. Belevtsev; A. Blaziene; P. Ciznar; E. Förster-Waldl; J. Kelecic; J. Marodi; E. Naumova; G. Nasrullayeva; K. Ress; M. Serban; et al. (Immunologic Research, 2020)

Primary immunodeficiencies in Central and Eastern Europe—the power of networking Report on the activity of the Jeffrey Modell Foundation Centers Network in Central and Eastern Europe - A. Sediva; M. Bataneant; M. Belevtsev; A. Blaziene; P. Ciznar; E. Förster-Waldl; J. Kelecic; J. Marodi; E. Naumova; G. Nasrullayeva; K. Ress; M. Serban; et al. (Immunologic Research, 2019)
Jeffrey Modell Foundation centers’ network activities in Central and Eastern Europe (JMF CEE) have contributed to the development of care for patients with primary immunodeficiencies. On the data continuously collected from individual centers in participating countries since 2011, we demonstrate a steady improvement in a number of aspects concerning complex care for patients with primary immunodeficiencies. The presented data show an improvement of awareness about these rare diseases across the whole Central and Eastern European region, an increase in newly diagnosed patients as well as genetically confirmed cases, earlier establishment of diagnosis, and improved access to clinical treatment. We also present an active patient involvement that is reflected in the expansion of patient organization centers and their activities. The cooperation within the JMF CEE network has also contributed to greater international exposure of participating centers and further to the gradual development of research activities in the rapidly evolving field of primary immunodeficiencies. The improvement of all important aspects of the complex field of primary immunodeficiencies within the JMF CEE network documents the strength and advantages of the joint and coordinated networking.

Effect of PACAP on Bacterial Adherence and Cytokine Expression in Intestinal Cell Cultures - A. Illes; G. Horvath; E. Schafer; M. Kerenyi; O. Karadi; B. Opper; G. Toth; D. Reglodi (International Journal of Peptide Research and Therapeutics, 2019)

Effects of Pituitary Adenylate Cyclase Activating Polypeptide in Human Proximal Tubule Cells Against Gentamicin Toxicity - G. Horvath; D. Reglodi; P. Czetany; A. Illes; Gy. Reman; A. Fekete; G. Toth; E. Laszlo; B. Opper (International Journal of Peptide Research and Therapeutics, 2019)

Ergodicity and parameter estimates in auditory neural circuits - Peter G. Toth; Petr Marsalek; Ondrej Pokora (Biological Cybernetics, 2018)

Plasticity in skeletal characteristics of nursery-raised staghorn coral, Acropora cervicornis - Ilsa B. Kuffner; Erich Bartels; Anastasios Stathakopoulos; Ian C. Enochs; G. Kolodziej; Lauren T. Toth; Derek P. Manzello (Coral Reefs, 2017)

Constraints to the adoption of fodder tree technology in Malawi - Gregory G. Toth; P. K. Ramachandran Nair; Colm P. Duffy; Steven C. Franzel (Sustainability Science, 2017)

Investigation of the Possible Functions of PACAP in Human Trophoblast Cells - G. Horvath; D. Reglodi; R. Brubel; M. Halasz; A. Barakonyi; A. Tamas; E. Fabian; B. Opper; G. Toth; M. Cohen; L. Szereday (Journal of Molecular Neuroscience, 2014)

Parasitic helminth infection in young cattle raised on silvopasture and open-pasture in Southeastern Brazil - R. M. A. de Mendonca; R. C. Leite; A. M. Q. Lana; J. O. Costa; G. Toth (Agroforestry Systems, 2014)

“Panta Rhei—Everything Flows”: Change in hydrology and society—The IAHS Scientific Decade 2013–2022 - A. Montanari; G. Young; H.H.G. Savenije; D. Hughes; T. Wagener; L.L. Ren; D. Koutsoyiannis; C. Cudennec; E. Toth; S. Grimaldi; G. Blöschl; M. Sivapalan; et al. (Hydrological Sciences Journal, 2013)

Effects of PACAP on Intracellular Signaling Pathways in Human Retinal Pigment Epithelial Cells Exposed to Oxidative Stress - E. Fabian; D. Reglodi; L. Mester; A. Szabo; K. Szabadfi; A. Tamas; G. Toth; K. Kovacs (Journal of Molecular Neuroscience, 2012)

Effects of Pituitary Adenylate Cyclase Activating Polypeptide on Human Sperm Motility - R. Brubel; P. Kiss; A. Vincze; A. Varga; A. Varnagy; J. Bodis; L. Mark; E. Jambor; G. Maasz; H. Hashimoto; Zs. Helyes; G. Toth; et al. (Journal of Molecular Neuroscience, 2012)

Effects of exercise stress on the endocannabinoid system in humans under field conditions - M. Feuerecker; D. Hauer; R. Toth; F. Demetz; J. Hölzl; M. Thiel; I. Kaufmann; G. Schelling; A. Choukèr (European Journal of Applied Physiology, 2012)

Catastrophe and the life span of coral reefs - Richard B. Aronson; William F. Precht; Ian G. Macintyre; Lauren T. Toth (Ecology, 2012)
A strong earthquake in the western Caribbean in 2009 had a catastrophic impact on uncemented, unconsolidated coral reefs in the central sector of the shelf lagoon of the Belizean barrier reef. In a set of 21 reef sites that had been observed prior to the earthquake, the benthic assemblages of 10 were eradicated, and one was partially damaged, by avalanching of their slopes. Ecological dynamics that had played out over the previous 23 years, including the mass mortalities of two sequentially dominant coral species and a large increase in the cover of an encrusting sponge, were instantaneously rendered moot in the areas of catastrophic reef‐slope failure. Because these prior dynamics also determined the benthic composition and resilience of adjacent sections of reef that remained intact, the history of disturbance prior to the earthquake will strongly influence decadal‐scale recovery in the failed areas. Geological analysis of the reef framework yielded a minimum return time of 2000–4000 years for this type of high‐amplitude event. Anthropogenic degradation of ecosystems must be viewed against the backdrop of long‐period, natural catastrophes, such as the impact of strong earthquakes on uncemented, lagoonal reefs.

Mice Deficient in Pituitary Adenylate Cyclase Activating Polypeptide (PACAP) are More Susceptible to Retinal Ischemic Injury In Vivo - K. Szabadfi; T. Atlasz; P. Kiss; B. Danyadi; A. Tamas; Zs. Helyes; H. Hashimoto; N. Shintani; A. Baba; G. Toth; R. Gabriel; D. Reglodi (Neurotoxicity Research, 2012)

Nutrition and division of labor: Effects on foraging and brain gene expression in the paper wasp Polistes metricus - T. H. F. DAUGHERTY; A. L. TOTH; G. E. ROBINSON (Molecular Ecology, 2011)
Deeply conserved molecular mechanisms regulate food‐searching behaviour in response to nutritional cues in a wide variety of vertebrates and invertebrates. Studies of the highly eusocial honey bee have shown that nutritional physiology and some conserved nutrient signalling pathways, especially the insulin pathway, also regulate the division of labour between foraging and non‐foraging individuals. Typically, lean workers leave the nest to forage for food, and well‐nourished workers perform tasks inside the nest. Here we provide the first direct test of whether similar mechanisms operate in a primitively eusocial insect in an independently evolved social lineage, the paper wasp Polistes metricus . We found that food deprivation caused reduced lipid stores and higher levels of colony and individual foraging. Individuals with greatly reduced lipid stores foraged at extremely elevated levels. In addition, brain expression of several foraging‐related genes was influenced by food deprivation, including insulin‐like peptide 2 ( ilp2 ). Together with previous findings, our results demonstrate that nutrition regulates foraging division of labour in two independently evolved social insect lineages (bees and wasps), despite large differences in social organization. Our results also provide additional support for the idea that nutritional asymmetries among individuals, based on differences in nutritional physiology and expression of conserved nutrient signalling genes in the brain, are important in the division of labour in eusocial societies.

Using multiple chemical indicators to characterize and determine the age of groundwater from selected vents of the Silver Springs Group, central Florida, USA - Leel Knowles; Brian G. Katz; David J. Toth (Hydrogeology Journal, 2010)

Changes in the Expression of Pituitary Adenylate Cyclase-Activating Polypeptide in the Human Placenta during Pregnancy and Its Effects on the Survival of JAR Choriocarcinoma Cells - R. Brubel; A. Boronkai; D. Reglodi; B. Racz; J. Nemeth; P. Kiss; A. Lubics; G. Toth; G. Horvath; T. Varga; D. Szogyi; E. Fonagy; et al. (Journal of Molecular Neuroscience, 2010)

Potential propagule sources for reestablishing vegetation on the floodplain of the Kissimmee River, Florida, USA - Arnold G. van der Valk; Louis A. Toth; Erin B. Gibney; Daniel H. Mason; Paul R. Wetzel (Wetlands, 2009)

Lipid stores, ovary development, and brain gene expression in Polistes metricus females - A. L. Toth; K. B. J. Bilof; M. T. Henshaw; J. H. Hunt; G. E. Robinson (Insectes Sociaux, 2009)

Binding of the novel radioligand [3H]UFP-101 to recombinant human and native rat nociceptin/orphanin FQ receptors - Massimo Ibba; Masato Kitayama; John McDonald; Girolamo Calo; Remo Guerrini; Judit Farkas; Geza Toth; David G. Lambert (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Agonistic Behavior of PACAP6-38 on Sensory Nerve Terminals and Cytotrophoblast Cells - D Reglodi; R Borzsei; T Bagoly; A Boronkai; B Racz; A Tamas; P Kiss; G Horvath; R Brubel; J Nemeth; G Toth; Z Helyes (Journal of Molecular Neuroscience, 2008)

Ecological threshold responses in European lakes and their applicability for the Water Framework Directive (WFD) implementation: synthesis of lakes results from the REBECCA project - Anne Lyche Solheim; Seppo Rekolainen; S. Jannicke Moe; Laurence Carvalho; Geoff Phillips; Robert Ptacnik; W. Ellis Penning; Laszlo G. Toth; Constance O’Toole; Ann-Kristin L. Schartau; Trygve Hesthagen (Aquatic Ecology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Fog Research: A Review of Past Achievements and Future Perspectives - I. Gultepe; R. Tardif; S. C. Michaelides; J. Cermak; A. Bott; J. Bendix; M. D. Müller; M. Pagowski; B. Hansen; G. Ellrod; W. Jacobs; G. Toth; et al. (Pure and Applied Geophysics, 2007)

A health risk assessment for fluoride in Central Europe - F. M. Fordyce; K. Vrana; E. Zhovinsky; V. Povoroznuk; G. Toth; B. C. Hope; U. Iljinsky; J. Baker (Environmental Geochemistry and Health, 2007)

Mixing of shallow and deep groundwater as indicated by the chemistry and age of karstic springs - David J. Toth; Brian G. Katz (Hydrogeology Journal, 2006)

New trends in marine chemical ecology - A. Ianora; M. Boersma; R. Casotti; A. Fontana; J. Harder; F. Hoffmann; H. Pavia; P. Potin; S. A. Poulet; G. Toth (Estuaries and Coasts, 2006)

Mixing of shallow and deep groundwater as indicated by the chemistry and age of karstic springs - David J. Toth; Brian G. Katz (Hydrogeology Journal, 2006)

Climate Impact Response Functions as Impact Tools in the Tolerable Windows Approach - H.-M. Füssel; F. L. Toth; J. G. van Minnen; F. Kaspar (Climatic Change, 2003)

Lack of phlorotannin induction in the kelp Laminaria hyperborea in response to grazing by two gastropod herbivores - Toth G.; Pavia H. (Marine Biology, 2002)

Restoration of wetland vegetation on the Kissimmee River Floodplain: Potential role of seed banks - Paul R. Wetzel; Arnold G. Valk; Louis A. Toth (Wetlands, 2001)

Detection and Quantification of Spongospora subterranea f. sp. subterranea in Soils and on Tubers Using Specific PCR Primers - Kenneth S. Bell; Jane Roberts; Susan Verrall; Daniel W. Cullen; Naomi A. Williams; Julian G. Harrison; Ian K. Toth; David E.L. Cooke; James M. Duncan; Jamie R. Claxton (European Journal of Plant Pathology, 1999)

Hypothesis testing with the similarity index - A. C. Leonard; S. E. Franson; V. S. Hertzberg; M. K. Smith; G. P. Toth (Molecular Ecology, 1999)
Multilocus DNA fingerprinting methods have been used extensively to address genetic issues in wildlife populations. Hypotheses concerning population subdivision and differing levels of diversity can be addressed through the use of the similarity index ( S ), a band‐sharing coefficient, and many researchers construct hypothesis tests with S based on the work of Lynch. It is shown in the present study, through mathematical analysis and through simulations, that estimates of the variance of a mean S based on Lynch’s work are downwardly biased. An unbiased alternative is presented and mathematically justified. It is shown further, however, that even when the bias in Lynch’s estimator is corrected, the estimator is highly imprecise compared with estimates based on an alternative approach such as ‘parametric bootstrapping’ of allele frequencies. Also discussed are permutation tests and their construction given the interdependence of S s which share individuals. A simulation illustrates how some published misuses of these tests can lead to incorrect conclusions in hypothesis testing.

Pharmacology of [Tyr1]nociceptin analogs: receptor binding and bioassay studies - K. Varani; A. Rizzi; G. Calo; R. Bigoni; G. Toth; R. Guerrini; S. Gessi; S. Salvadori; P.A. Borea; D. Regoli (Naunyn-Schmiedeberg's Archives of Pharmacology, 1999)

Preliminary Studies on the Population Genetics of the Central Stoneroller (Campostoma anomalum) from the Great Miami River Basin, Ohio - R. N. Silbiger; S. A. Christ; A. C. Leonard; M. Garg; D. L. Lattier; S. Dawes; P. Dimsoski; F. McCormick; T. Wessendarp; D. A. Gordon; A.C. Roth; M. K. Smith; et al. (Environmental Monitoring and Assessment, 1998)